2015
DOI: 10.18632/oncotarget.2898
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 functions as a regulator of cell self-renewal by interacting with the β-catenin pathway in hepatocellular carcinoma

Abstract: The Notch signaling pathway plays a role in cell proliferation, differentiation. Emerging data have revealed aberrant Notch3 expression in hepatocellular carcinoma (HCC). However, whether Notch3 plays a role in tumorigenesis or tumor progression is unclear. In this study, we found that over 71.8% of the cases studied had high Notch3 expression levels (n = 32); Notch3 expression positively correlated with alpha-fetoprotein (AFP) levels (p = 0.0311) and negatively correlated with the differentiation grade (p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 24 publications
7
32
0
Order By: Relevance
“…Notch3 was identified as a positive marker associated with aggressive traits and short survival in HCC, since patients with high levels of Notch3 expression commonly had a poor prognosis (13). The present authors also reported that Notch3 expression is inversely correlated with beta-catenin content but positively associated with the protein level of Nanog, thus confirming that Notch3 serves a role in modulating the stemness of tumor cells via the inactivation of the Wnt/beta-catenin pathway (14). Patients with high Notch1 or Notch3 expression were at a significantly increased risk for shortened survival time (15).…”
Section: Introductionsupporting
confidence: 81%
“…Notch3 was identified as a positive marker associated with aggressive traits and short survival in HCC, since patients with high levels of Notch3 expression commonly had a poor prognosis (13). The present authors also reported that Notch3 expression is inversely correlated with beta-catenin content but positively associated with the protein level of Nanog, thus confirming that Notch3 serves a role in modulating the stemness of tumor cells via the inactivation of the Wnt/beta-catenin pathway (14). Patients with high Notch1 or Notch3 expression were at a significantly increased risk for shortened survival time (15).…”
Section: Introductionsupporting
confidence: 81%
“…As potent tumorigenic potential is one of the most important properties of cancer stem cells [48], these suspended lymphoma cells can be regarded as cancer stem-like cells. Notch activation has been found to correlate with cancer stem cell characteristics [49-51]. Our findings also confirm that inhibition of Notch signaling by DAPT can abolish the emergence of highly tumorigenic lymphoma cells.…”
Section: Discussionsupporting
confidence: 85%
“…While it is possible that a decrease or disruption of Wnt/β-catenin signaling further enhanced HCC in TKOβcat mice through another mechanism(s) that is yet to be defined, the important clinical findings reported by Fitamant et al that signatures of β-catenin activation and YAP activation are mutually exclusive in HCC human patients (80) strongly suggest that it is unlikely that Wnt/β-catenin activation contributed to the development of HCC development in Hippo-DKO mice. In contrast, YAP and Notch activation signatures are highly correlated in HCC (80,81), arguing for the clinical importance of the Notch and YAP/TAZ positive feedback loop we identified in this study. Therefore, inhibition of this positive feedback loop by Wnt/β-catenin is at least one of the underlying mechanisms whereby HCC development in DKO mice was further enhanced upon β-catenin removal.…”
Section: Discussionmentioning
confidence: 56%